Measures Undertaken in China to Avoid COVID-19 Infection: Internet-Based, Cross-Sectional Survey Study - Huang, Yu; Wu, Qingqing; Wang, Ping; Xu, Yan; Wang, Lei; Zhao, Yusui; Yao, Dingming; Xu, Yue; Lv, Qiaohong; Xu, Shuiyang (JMIR Publications, 2020)
BackgroundIn early 2020, over 80,000 cases of coronavirus disease (COVID-19) were confirmed in China. Public prevention and control measures, along with efforts from all sectors of society, were undertaken to control and eliminate disease transmission. ObjectiveThis paper describes Chinese citizens' response to the epidemic, the preventive measures they implemented to avoid being infected, and the public strategies that were carried out by the government, health workers, etc. We also discuss the efficacy of these measures in controlling the epidemic in China. MethodsInformation on the responses and behaviors of Chinese citizens were collected through a cross-sectional, internet-based survey using Dingxiang Doctor's public account on WeChat. Information on public strategies implemented by all sectors of society to control the epidemic and data on new COVID-19 cases were collected from the internet, mainly from government websites. Standard descriptive statistics and multivariate logistic regression analyses were conducted to analyze the data. ResultsA total of 10,304 participants responded to the survey, with 10,198 valid responses; 74.1% (n=7557) were female and 25.9% (n=2641) were male. Overall, 98.2% (n=10,013) of participants paid high or very high attention to the epidemic, with WeChat being their main information source (n=9400, 92.2%). Over half the participants (n=5878, 57.7%) were confident that the epidemic could be curbed in China; 92.4% (n=9427) opened windows for ventilation more frequently than usual; 97.9% (n=9986) used masks in public; 95.7% (n=9759) avoided large crowds and stayed at home as much as possible; and 97.9% (n=9988) washed their hands more often than usual. Women were more likely to practice these behaviors than men (P<.001). With a series of strict public control measures, like nationwide health education campaigns, holiday extensions, the Examine and Approve Policy on the resumption of work, close management of working and living quarters, a health QR (Quick Response) code system, community screening, and social distancing policies, the number of new cases have decreased dramatically since February 12, 2020. ConclusionsThe methods employed by Chinese citizens and authorities have effectively curtailed the spread of COVID-19, demonstrating that this pandemic can be brought under control as long as the right measures are taken.